2019
DOI: 10.3390/s19194199
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Artificial Potential Field-Based Autonomous Vehicle Safety Control with Interference of Lane Changing in Mixed Traffic Scenario

Abstract: Car-following is an essential trajectory control strategy for the autonomous vehicle, which not only improves traffic efficiency, but also reduces fuel consumption and emissions. However, the prediction of lane change intentions in adjacent lanes is problematic, and will significantly affect the car-following control of the autonomous vehicle, especially when the vehicle changing lanes is only a connected unintelligent vehicle without expensive and accurate sensors. Autonomous vehicles suffer from adjacent veh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 34 publications
0
25
0
Order By: Relevance
“…W ITH the rapid development in wireless communication technology, the application of wireless sensor networks (WSNs) has rapidly increased, such as those in wildlife protection [1], environmental monitoring [2], traffic management [3], disaster management [4], and medical care [5]. Owing to the wireless medium and constrained nature of resources [6] of the sensors used in WSNs, source location privacy (SLP) faces more severe challenges compared to traditional networks.…”
Section: Introductionmentioning
confidence: 99%
“…W ITH the rapid development in wireless communication technology, the application of wireless sensor networks (WSNs) has rapidly increased, such as those in wildlife protection [1], environmental monitoring [2], traffic management [3], disaster management [4], and medical care [5]. Owing to the wireless medium and constrained nature of resources [6] of the sensors used in WSNs, source location privacy (SLP) faces more severe challenges compared to traditional networks.…”
Section: Introductionmentioning
confidence: 99%
“…Driven by the labor shortage, the need for safe production processes, and people's demand for a comfortable life, automation technology has gradually penetrated every aspect of production and life in recent decades [1,2]. For example, automated guided vehicles (AGV) have been broadly applied to the handling of heavy objects or large devices in production environments [3], multi-axis CNC machines have been extensively used to machine parts with sculptured surfaces in the fields of machinofacture and aerospace [4], robots have been developed for welding, spraying and assembling in smart factories [5], firefighting robots have come into service in order to reduce the risks that human firefighters face [6], the Roomba promises its customers "effortless cleaning" or robot vacuums allow owners to "clean your floors without lifting a finger" [7], and feeding assistive robots have been proposed to help older people and people with disabilities in their daily life [8].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome this practical hurdle, a heading-error-based first order linear active disturbance rejective controller (HFO-LADRC) is proposed in this paper. The main contributions of this manuscript are as follows: (1) A new lateral error model is proposed according to the kinematic relationship of the preview node, fixed onto the vehicle body, and the track node, located in the reference trajectory, in order to describe the lateral motion of an autonomous road sweeper. The model shows that the system is underactuated.…”
Section: Introductionmentioning
confidence: 99%
“…An air gap membrane distillation module with energy recovery can be used for desalination experiments and the system can be optimized using response surface methodology [21]. The parameters of cold feed inlet temperature (T1), hot feed inlet temperature (T3) and feed flow rate (F) are considered, and the membrane flux (J) and thermal efficiency (GOR) are the targets [22]. Based on the regression model, it was found that T3 had the greatest impact on both J and GOR.…”
Section: Introductionmentioning
confidence: 99%